TEACHERS’ STRATEGY IN TEACHING WRITING BY ONLINE APPLICATION AT MTS N 2 MEDAN - Fauziah Tambak; Indra Hartoyo (Universitas Negeri Medan, 2021)
This study discusses the strategies that teachers use when learning through online applications. This investigation raises the main problem, namely